Au prisme de Louise Weiss ? Les femmes dans les mouvements d’assistance aux réfugiés en France durant la Première Guerre mondiale - Ronan Richard (Genre & Histoire)
During the First World War, many relief committees were created to assist the two million refugees. Some of these organizations were improvised on the arrival of convoys by women determined to serve the nation at war and to become involved in helping the victims of the conflict. This was the case of Louise Weiss, then a young student, who founded a committee in Saint-Quay-Portrieux, on the Breton coast. Other women’s organizations existed before the war, such as local branches of the National Council of French Women and the Union of Women of France. From 1915, the network of these social assistance committees began to be structured. The biggest official organizations still included many women, all from local elites. But they were excluded from the positions of executive responsibilities. As the wives of prefects, mayors or other notables, they often represented their husbands but also acted to give themselves a profile. This compassionate self-promotion must not overshadow the work of independent women’s committees. Often set up early on, in many places they compensated for the inertia of public authorities and served as models when the authorities set up institutional committees where gender relations always favored men.